MATHEMATICS LITERACY ANALYSIS REVIEWED FROM JUNIOR HIGH SCHOOL STUDENTS' ADVERSITY QUOTIENT - Gunawan, Gunawan; Hafizh, Faizal Abdul; Kusuma, Jaka Wijaya (Yayasan Education and Social Center, 2025)
Mathematical literacy is an essential skill of the 21st century, while AQ provides a non-cognitive perspective that has been under-appreciated in the study of mathematical literacy. This study aims to analyze the mathematical literacy ability of junior high school students reviewed from the Adversity Quotient (AQ), which is the ability of individuals to face challenges and pressures in the learning process. This study uses a qualitative approach of case studies with the subjects of grade VIII students of SMP Istiqomah Sambas Purbalingga who were selected based on the high, medium, and low AQ categories. Data collection techniques include context-based tests, in-depth interviews, and document analysis of student work. The results of the study showed that students with high AQ (climber type) were able to formulate mathematical problems from the context of the problem, compile the SPLDV model, and interpret the results accurately. Students also show high self-control, responsibility, and perseverance. On the other hand, students with moderate AQ (camper) have mathematical representation skills but are less thorough in interpreting results, while students with low AQ (quitter) have difficulty in compiling mathematical models and easily give up. These findings can be the basis for designing learning that strengthens students' character and fighting power in mathematics